Women's rights in the world and in Perú - Pérez Sánchez Cerro, José Luis (2021)
The rights of women and girls are human rights. They cover all aspects of life, namely health, education, political participation, economic well-being, not being the object of violence and many more. They have the right to the full and equal enjoyment of all their human rights and to live free from all forms of discrimination. Their protection must be enshrined in national laws and policies firmly rooted in international human rights standards. For this, it is important that national laws recognize their rights and that they have the capacity to vindicate them and fight for gender equality. Discrimination on the grounds of sex is prohibited in almost all human rights treaties, which also includes the International Covenant on Civil and Political Rights and the International Covenant on Economic, Social and Cultural Rights, which by virtue of article 3, common to both ensure men and women equal rights to all enunciated in these documents. There are treaties and expert bodies specifically dedicated to making women's human rights a reality, such as the “Convention on the Elimination of All Forms of Discrimination Against Women” (CEDAW), which is considered the International Bill of Women's Rights. It defines what discrimination against women is and establishes a national action program to put an end to it. The Convention was approved by the United Nations in 1979 and entered into force on September 3, 1981.